Students’ Perceptions of Speculative Design with Generative AI in Creating Futuristic Narratives: An Interdisciplinary Study with Undergraduate Students from Diverse Fields - Loutfi, Marcelo Soares; Tibau, Marcelo; Gimenez, Paulo J. A.; Siqueira, Sean Wolfgand Matsui (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2025: Anais do XXI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2025.246596, 2025)
Context: This study explores the integration of speculative design (SD) and Generative Artificial Intelligence (GenAI) in educational and interdisciplinary contexts. The goal is to prepare students to face future technological complexities, emphasizing ethical and social considerations. Problem: The research addresses the need to equip students with critical skills to engage with emerging technologies. Challenges include the usability of GenAI tools, the lack of ethical frameworks for responsible innovation, and the need for creative approaches to envision future scenarios. These challenges have technological, social, and educational dimensions. Solution: A participatory workshop that integrates SD and GenAI to inspire creativity and ethical reflection, enabling participants to collaboratively explore future technological implications. Information Systems Theory: The research draws on Actor-Network Theory (ANT) and speculative realism to analyze the dynamic interactions between human and non-human actors in sociotechnical networks. Method: The research employed a participatory design methodology, conducting a workshop with 17 undergraduate students from diverse fields. A qualitative approach was used to examine data collected through focus groups. The analysis focused on identifying themes related to user experiences and ethical considerations. Summary of Results: Four main themes emerged: engagement with the process, the applicability of GenAI, personal impact and recommendations, and ethical and social reflections. Participants valued SD as a critical tool for analyzing ethical implications and the social effects of speculative technologies. Contributions and Impact on IS: The study offers an innovative framework that combines SD and GenAI, promoting ethical and inclusive educational practices and contributing to more responsible sociotechnical systems.